A Lamellar MWW Zeolite With Silicon and Niobium Oxide Pillars: A Catalyst for the Oxidation of Volatile Organic Compounds. Issue 46 (9th August 2020) - Schwanke, Anderson Joel; Balzer, Rosana; Wittee Lopes, Christian; Motta Meira, Débora; Díaz, Urbano; Corma, Avelino; Pergher, Sibele
Abstract: In this work, an MWW‐type zeolite with pillars containing silicon and niobium oxide was synthesized to obtain a hierarchical zeolite. The effect of niobium insertion in the pillaring process was determined by combining a controllable acidity and accessibility in the final material. All pillared materials had niobium occupying framework positions in pillars and extra‐framework positions. The pillared material, Pil‐Nb‐4.5 with 4.5 wt % niobium, did not compromise the mesoporosity formed by pillaring, while the increase of niobium in the structure gradually decreased the mesoporosity and ordering of lamellar stacking. The morphology of the pillared zeolites and the niobium content were found to directly affect the catalytic activity. Specifically, we report on the activity of the MWW‐type zeolites with niobium catalyzing the gas‐phase oxidation of volatile organic compounds (VOCs), which is an important reaction for clean environmental. All produced MWW‐type zeolites with niobium were catalytically active, even at low temperatures and low niobium loading, and provided excellent conversion efficiencies. Abstract : 2D zeolites containing pillars of silicon and niobium oxide and material containing 4.5 wt % of Nb showed interlamellar mesopores and higher oxidation performance than other catalysts containing gold and palladium. The higher oxidation of benzene reaching 86 % occurred with the catalyst containing 14.8 wt % of Nb.